2014
DOI: 10.4172/2165-8048.1000179
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids Effect on Bone Mineral Density: A Pilot Study in Apparently Healthy Syrians

Abstract: Objective: Dyslipidemia is suggested to be one of factors that affect bone mineral density (BMD). However, epidemiological studies concerning relationship between serum lipids and BMD showed different results. Absent, positive, or negative relations have been reported.The aim of this study was to investigate the correlation between serum lipids and BMD in a group of apparently healthy Syrians. Methods:This pilot cross-sectional study was carried out at one of Damascus University Hospitals. 152 apparently healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Sung et al [ 38 ] reported that TG levels were not correlated with BMDs in elderly Korean men. Lilianne et al [ 40 ] failed to observe significant correlations between TG levels and BMDs measured at various skeletal sites, such as the lumbar spine, femoral neck, and total hip. Li et al [ 41 ] did not identify an association between TG levels and BMD in postmenopausal Chinese women.…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al [ 38 ] reported that TG levels were not correlated with BMDs in elderly Korean men. Lilianne et al [ 40 ] failed to observe significant correlations between TG levels and BMDs measured at various skeletal sites, such as the lumbar spine, femoral neck, and total hip. Li et al [ 41 ] did not identify an association between TG levels and BMD in postmenopausal Chinese women.…”
Section: Discussionmentioning
confidence: 99%